Conception of Manor in the Lithuanian Worldview - Smetona, Marius; Lisauskaitė, Agnė; Mierkytė, Greta; Vaitkutė, Ieva (Tautosakos darbai, 2019)
Linguistic studies focusing on manors are rather scarce. The conception of manor mainly appears in historical and literary discourses. Research articles by historians most frequently focus on history, cultural significance and heritage of individual manors rather than on analysis of the history of manors in general. After WWI, when aristocracy lost its privileges, new manor estates ceased being established. The old ones started to deteriorate and this process particularly accelerated during the Soviet occupation. The restoration of Lithuanian independence significantly increased the public interest in manors. The buildings in question underwent restoration and started serving as venues for cultural events. Currently, manors attract high numbers of tourists.The semantic field of the manor is broadly revealed in Lithuanian literature. Works by Lithuanian authors and writers of Lithuanian origins, like “Metai” (The Seasons) by Kristijonas Donelaitis, “Sename dvare” (In the Old Manor) by Šatrijos Ragana, “Altorių šešėly” (In the Shadow of Altars) by Vincas Mykolaitis-Putinas, “Isos slėnis” (The Issa Valley) by Czesław Miłosz, “Skirgaila” (Skirgaila) by Vincas Krėvė, or “Ponas Tadas” (Sir Thaddeus) by Adam Mickiewicz present a multi-layered conception of manor. Some literary works depict manors as places of peasant exploitation, while manor masters engaged in their customs and traditions appear as forming a separate world. Other works tell stories about peasants, who experience no neglect in the manor estates and even receive help or sympathy from the representatives of the nobility. Manors also stand out as cultural centers.The image of manor is far from homogenous in the Lithuanian worldview. One could safely say that the old conception of manor has survived until nowadays; however, it is now supplemented with perception adopted from literary works and functions of the extant manors. Firstly, manors are undoubtedly related to certain specific historical and cultural period. The manor symbolizes the past, which attempts speaking again but is suppressed by external factors and the current pace of life. The manor embodies history not only as a building with its surroundings, but reminds the present-day Lithuanians of the social roles in old times through its functions performed in the past. Contemporary Lithuanians perceive the historical aspect of manor and its role in the social, cultural and property-based social layers, although their understanding of manor as an economic entity has significantly deteriorated. However, new semes related to politics, enterprise, tourism, or functioning of manors as museums or a mystical places are also evident. The latter stems from literature, fairy tales, and proverbs.
Keywords: manor; concept; ethno-linguistics; folklore